An ultrathin porphyrin-based metal-organic framework for efficient photocatalytic hydrogen evolution under visible light. (August 2019) - Wang, Xin; Zhang, Xueliang; Zhou, Wei; Liu, Lequan; Ye, Jinhua; Wang, Defa
Abstract: Development of inorganic semiconductor photocatalysts for efficient photocatalytic production of clean and renewable hydrogen has long been attracting tremendous attentions. Herein, we report an ultrathin porphyrin-based metal-organic framework (PMOF) with Ti-oxo clusters, exhibiting a photocatalytic hydrogen evolution rate of as high as 8.52 mmol⋅g −1 ⋅h −1 in the presence of Pt as cocatalyst under a wide range of visible light irradiation up to 700 nm. The photocatalytic reaction over PMOF is a typical ligand-to-metal charge transfer (LMCT) process, i.e., the photoinduced electrons transfer from porphyrin-based ligands (light harvester) to Ti-oxo clusters (catalytic center), and thereby the charge carriers' separation is significantly enhanced. Moreover, the long-term course reaction confirms the excellent water-resistance and photo-stability of PMOF in photocatalytic hydrogen evolution. Graphical abstract: An ultrathin porphyrin-based metal-organic framework (PMOF) with Ti-oxo clusters exhibits efficient photocatalytic hydrogen evolution under a wide range of visible-light irradiation.Image 1 Highlights: Ultrathin porphyrin-based MOF (PMOF) shows high water-resistance and photostability. Efficient photocatalytic H2 evolution over PMOF under wide range visible light. Porphyrin-based ligands harvest light; Ti-oxo clusters act as catalytic center. The ligand-to-metal charge transfer plays a role in photocatalytic H2 evolution.